In Pursuit of Police Ethics: An Analysis of Ethics Content in State-Mandated Basic Police Training Curricula. (4th May 2022) - Cohen, Galia
Abstract: Recent events of police misconduct sparked a nationwide debate on the effectiveness of police ethics training. In this article, we ask: do basic police academies prepare future police officers to be the ethical decisions makers we expect them to be? By utilizing a mixed methods research design with content analysis, we evaluate the way ethics training for police recruits is structured in terms of content and quantity (i.e., training hours) across the 50 states. More specifically, we use a four-part interpretive framework to analyze state-mandated basic training curricula for (1) the rationale for teaching ethics (2) approaches to teaching ethics (3) the law enforcement ethos, and (4) ethics control mechanisms. The article concludes by offering practical recommendations on how to improve ethical competencies in police training and practice.